2017
DOI: 10.1016/j.jcin.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenting

Abstract: The incidence of PP in CAS was 2.6%, with a high risk of ischemic complications if PP was observed. The present findings indicate the necessity of appropriate device selection to avoid PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Atherosclerotic plaque protrusion through conventional carotid stent struts [ 8 , 56 59 ] has been identified as a leading mechanism of post-procedural cerebral embolisation [ 55 ] and post-procedural adverse neurological events seen with the prior generation of carotid stents [ 47 , 48 , 50 , 54 ]. Vascular surgery key opinion leaders have repeatedly indicated that the safety of CAS needs to be improved before CAS can be routinely applied by surgeons as an alternative to CEA [ 68 , 69 ], and that the CAS role in carotid revascularisation would be fully established only with an increased use of proximal neuroprotection systems and the development of novel “ultra-closed” cell stent systems [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Atherosclerotic plaque protrusion through conventional carotid stent struts [ 8 , 56 59 ] has been identified as a leading mechanism of post-procedural cerebral embolisation [ 55 ] and post-procedural adverse neurological events seen with the prior generation of carotid stents [ 47 , 48 , 50 , 54 ]. Vascular surgery key opinion leaders have repeatedly indicated that the safety of CAS needs to be improved before CAS can be routinely applied by surgeons as an alternative to CEA [ 68 , 69 ], and that the CAS role in carotid revascularisation would be fully established only with an increased use of proximal neuroprotection systems and the development of novel “ultra-closed” cell stent systems [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic carotid artery stenosis continues to be a major cause of acute ischaemic strokes [ 1 4 ]. Accordingly, patients with symptomatic carotid stenosis account for up to ~30–60% of subjects enrolled in contemporary clinical trials of carotid revascularisation [ 5 8 ]. Some of these patients develop symptoms of carotid stenosis-associated cerebral ischaemia despite optimised medical therapy (OMT) [5, 9 12 ], consistent with the concept that OMT may reduce or delay [ 10 , 13 ], but does not abolish, the stroke risk in relation to carotid atherosclerosis [ 9 , 10 , 12 ].…”
Section: Atherosclerotic Carotid Stenosis and Ischaemic Strokementioning
confidence: 99%
See 2 more Smart Citations
“…[ 22 23 24 ] Several factors related to post-CAS restenosis have been reported, including demography, comorbidity, and/or characters of original plaques, e.g., age,[ 4 22 ] female gender,[ 22 ] symptomatic cases,[ 13 ] diabetes,[ 5 22 ] hypertension,[ 22 40 ] hyperlipidemia,[ 22 ] inflammation markers,[ 37 ] high-degree stenosis,[ 32 ] and length of the plaques,[ 31 ] although some of these studies merely conducted univariate or combined analyses with restenoses after carotid endarterectomy (CEA). Several researchers reported CAS-procedure-related factors of post-CAS restenosis, such as immediate residual stenosis,[ 7 31 40 ] double stent deployment,[ 7 ] use of an open-cell stent,[ 20 ] and the predilation balloon diameter. [ 32 ]…”
Section: Introductionmentioning
confidence: 99%